HUBUNGAN KETERAMPILAN MEMBACA KRITIS DENGAN KETERAMPILAN MENULIS ARTIKEL POPULER BERDASARKAN GAYA BELAJAR SISWA KELAS XI SMA NEGERI 5 PADANG - Najmi Hayati; Atmazaki .; Abdurahman . (Bahasa, Sastra, dan Pembelajaran, 2014)
Abstract: This research is purposed to explain subsequent concerns. Describe the relationship between student’s critical ability and student’s popular-article writing skill in class XI SMA Negeri 5 Padang and describe the relationship between critical reading ability and popular-article writing skill based on student’s visual learners, auditory learners,  tactual learners at class XI SMA Negeri 5 Padang. This correlation research is taken population of students in class XI SMA Negeri 5 Padang year of school 2013/2014. Sample collection in 30 students this research is conducted by using proportional random sampling. Research instrumen is objective test to critical reading, working test to popular-article writing skill and questionnaire to learning style. data were analyzed b describe correlation.This research find out the magnitude of relationship between critical reading ability and popular-article writing skill, whether individually or collectively, based on student’s learning style.The result of the research indicated that (1) there is a significant relationship between student’s critical reading ability and popular-article writing skill at the rate of 0.466; (2) There is a significant relationship between student’s critical reading ability and popular-article writing skill based on visual learners at the rate of 0.61; (3) There is a significant relationship between student’s critical reading ability and popular-article writing skill based on auditory learners at the rate of 0.633; (4) There is a significant relationship between student’s critical reading ability and popular-article writing skill based on tactual learners at the rate of 0.52. It can be concluded that critical reading ability, as individually or collectively, have a contribution in student’s popular-article writing skill in class XI SMA Negeri 5 Padang. Keywords: critical reading ability, popular-article writing skill, learning style